Evaluation of the stock enhancement effect of Phascolosoma esculenta on macrobenthic communities using diversity and biotic indices in Yueqing Bay, East China Sea - Yang, Yushu; Song, Chen; Chen, Peng; Lu, Wuyang; Han, Qingxi (Frontiers in Marine Science, 2024)
Stock enhancement activities have many benefits but also negative impacts. The macrobenthic diversity index and the M-AMBI index were adopted to assess the effects of stock enhancement of Phascolosoma esculenta on macrobenthic communities and the local ecosystem in Yueqing Bay. The results revealed that the Shannon–Wiener diversity index (H’) and Margalef richness index (d) increased in October 2022 after stock enhancement, indicating a positive ecological restoration effect. The average M-AMBI in the intertidal zone of Yueqing Bay was 0.59, indicating good benthic ecological quality. Excluding seasonal factors, the M-AMBI in the intertidal zone increased after stock enhancement, indicating that stock enhancement by Phascolosoma esculenta had a certain positive effect on the intertidal ecological environment of Yueqing Bay. The increase in the M-AMBI occurred mainly in the low-tide zone, increased slightly in the mid-tide zone, and remained basically unchanged in the high-tide zone. On the one hand, Phascolosoma esculenta can accumulate heavy metals from the environment and release a large amount of organic matter throughout its lifecycle, promoting nutrient cycling, which plays a positive role in the environment. On the other hand, Phascolosoma esculenta is an economic species; however, the planting of mangroves in the low tide zone causes fishers to fish in the mid- and high-tide zones, so the changes in the M-AMBI values in each tidal zone are related mainly to Phascolosoma esculenta and anthropogenic disturbances.